Cocaine Dependent Individuals and Gamblers Present Different Associative Learning Anomalies in Feedback-Driven Decision Making: A Behavioral and ERP Study - Torres, Ana; Catena, Andrés; Cándido, Antonio; Maldonado, Antonio; Megías, Alberto; Perales, José C. (Frontiers in Psychology, 2013)
Several recent studies have demonstrated that addicts behave less flexibly than healthy controls in the probabilistic reversal-learning task (PRLT), in which participants must gradually learn to choose between a probably-rewarded option and an improbably-rewarded one, on the basis of corrective feedback, and in which preferences must adjust to abrupt reward contingency changes (reversals). In the present study, pathological gamblers (PG) and cocaine-dependent individuals (CDI) showed different learning curves in the PRLT. PG also showed a reduced electroencephalographic response to feedback (Feedback-Related Negativity, FRN) when compared to controls. CDI’s FRN was not significantly different either from PG or HC’s. Additionally, according to sLORETA analysis, cortical activity in regions of interest (previously selected by virtue of their involvement in FRN generation in controls) strongly differed between CDI and PG. However, the nature of such anomalies varied within-groups across individuals. Cocaine use severity had a strong deleterious impact on the learning asymptote, whereas gambling intensity significantly increased reversal cost. These two effects have remained confounded in most previous studies, which can be hiding important associative learning differences between different populations of addicts.